The repatriation of returning ISIS foreign terrorist fighters: Analysis of the factors influencing Indonesia's refusal and its implications on counterterrorism efforts - Anns, Muhammad; Syauqillah, Muhamad (Faculty of Social and Political Science, Universitas Airlangga, 2023)
The purpose of this paper is to study about repatriation of Foreign Terrorist Fighters (FTFs) to Indonesia who went to Syria by analyzing the factors such as risk of involving in terrorist attacks in Indonesia, which are influencing Indonesia's refusal and its implications on a state's counterterrorism efforts. The present study is carried out using qualitative research method and the data collected from secondary sources including research articles, newspapers and books related to the FTF phenomenon. To address this issue, the Indonesian government is considering a strategy to minimize negative consequences from the return of Indonesian individuals associated with terrorist activities from overseas. The results show that the Indonesian government has calculated the benefits and drawbacks of either returning foreign terrorist fighters' home or not. In the process, the government ultimately decided against the FTFs' repatriation, citing the need to safeguard millions of people's security from the danger of terrorism as a national priority for Indonesia. It concludes that the accepting repatriation of FTF by Indonesia would support human rights efforts in giving them fair trials if they have committed crimes and it will prevent them from being stateless.